The Language of the Legal Text ; A Comparative Linguistic Study - et. al., Alaa Naji Jassim Al-Mawla, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Terms have a great importance for any language, especially in showing rules or judgments, so semantics is selected to be the title of this study. The study focuses on the terms of the legal text, so it is entitled(Between the linguistic and the legal text/A comparative study); the legal text is preceded by the linguistic term because the study is specialized in Arabic language (linguistic branch ), hence we refer to the linguistic lexicons and the semantics books whose authors are called (Semantics Linguists). Then we compared them with the writes of legislators and scholars whom we called (The authors of the texts or The drafters ). Legislators and legalists are aware of the impact of these connotations as they concerning the resulting judgments. Since that legislation terms have a deep connection with people life, drafters were so careful to select the accurate terms so we refer to semantics and to the word and its meaning. There is no doubt that the words are not indicative in their meaning in themselves or with the aid of a context, so we put that according to what was known to the jurists, such as flexible ,vague and confused. We have chosen two models of Iraqi law, one of which is known as the Civil Law and the Penal Law. The results could be summarized as following: legislative terms significance is affected by the terms significances for the semantic linguists, Usulis and logicians; the research reveals this point in making the text a means to reveal the term significance. For the terms( speech and situation), which are the products of the semantic linguists, we found them for the drafters. One of the aspects of the semantics effect is that they have a special significance for each term, while for the Usuli effect we have the terms which they put for the word meaning, and for the logicians we have the external issue which means terms significance according to the circumstances.